2014
DOI: 10.3855/jidc.4525
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C prevalence among heroin addicts in methadone maintenance treatment (MMT) and not in MMT in Pereira, Colombia

Abstract: This item has no abstract. Follow the links below to access the full text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
1
2
0
2
Order By: Relevance
“…There are few studies on hepatitis C in Colombia 32 , and this investigation identified a significant number of injection drugs users who share and reuse injection equipment, similarly to what was observed in other cities of Colombia in 2010 [33][34][35] ; widely documented and discussed factors in other countries, though for Colombia, represent the first step toward intervention strategies 36 . Co-infections of HIV and HCV have been reported among drug users in different countries.…”
Section: Discusionsupporting
confidence: 62%
“…There are few studies on hepatitis C in Colombia 32 , and this investigation identified a significant number of injection drugs users who share and reuse injection equipment, similarly to what was observed in other cities of Colombia in 2010 [33][34][35] ; widely documented and discussed factors in other countries, though for Colombia, represent the first step toward intervention strategies 36 . Co-infections of HIV and HCV have been reported among drug users in different countries.…”
Section: Discusionsupporting
confidence: 62%
“…En Colombia, se ha determinado la prevalencia de la enfermedad en algunos grupos de riesgo, y se ha observado un incremento de los casos en quienes recibieron transfusiones antes de 1994 (6,7), en pacientes con enfermedad renal crónica terminal (8), en adictos al uso de drogas por vía parenteral (9,10), entre el personal sanitario (11,12) y en población indígena (12,13). Sin embargo, la persistente búsqueda de personas infectadas en los grupos de riesgo tradicionales no ha permitido detectar otros factores potencialmente implicados en el contagio.…”
unclassified
“…Por otra parte, la prevalencia de la hepatitis C en algunas poblaciones de riesgo no ha sido uniforme en las diferentes zonas del país (9,10,12,13), lo cual implica que los factores asociados a la infección pueden variar en función de diferencias geográficas y culturales.…”
unclassified
“…However, some MMT patients are still at risk of craving heroin; these patients may relapse to heroin abuse, which may adversely affect their HRQoL [38,39]. Third, patients with syringe sharing are at high risk of HIV, HCV, or hepatitis B virus (HBV) infection that can lead to acquired immunodeficiency virus, chronic hepatitis C, or chronic hepatitis B, respectively, which would also deteriorate the HRQoL [34,40,41]. Therefore, the side effects of methadone should be carefully considered and addressed during long-term MMT.…”
Section: Discussionmentioning
confidence: 99%